The scientific evidence for the role of milk protein-derived bioactive peptides in humans: A Review. (August 2015) - Nongonierma, Alice B.; FitzGerald, Richard J.
Highlights: Milk proteins are a good source of bioactive peptides (BAPs). A limited number of BAPs have been reported in human biological fluids and tissues. Controversial results on the role of BAPs in human health have been reported. Low bioavailability and confounding factors may explain the controversial results. Abstract: Milk proteins are a good source of bioactive peptides (BAPs). BAPs can positively affect various health biomarkers in vitro . The role of milk protein-derived BAPs in humans was reviewed herein. To date, a limited number of BAPs have been identified in the gastrointestinal tract of humans and in the circulation at concentrations which may be sufficient to mediate in vivo bioactivity. While the outcomes of several human intervention studies have shown promising results, some studies have failed to demonstrate additional health benefits. This may be related to a low potency and bioavailability of the BAPs evaluated as well as confounding factors (i.e. genotype, health status and other sources of inter-individual variability). Universal guidelines for the evaluation of BAPs in humans such as adequately powered double-blind randomised clinical trials are needed.